Transforming food retail for better health: The Healthy Stores 2020 trial. (30th September 2020) - Brimblecombe, J; McMahon, E; De Silva, K; Ferguson, M; Miles, E; Wycherley, T; Peeters, A; Minaker, L; Greenacre, L; Mah, C
Abstract: Background: How food is promoted in food retail settings impacts population diet. Foods high in sugar, fat and/or salt are promoted by retailers to attract impulse purchases. To combat the high burden of chronic disease and associated conditions confronting society we examined the impact of restricted retail merchandising (promotion and visibility) of discretionary food and beverages on sales and business outcomes. Methods: We conducted a pragmatic randomised controlled trial in partnership with a retail organisation operating stores in remote communities of Australia (the Arnhem Land Progress Aboriginal Corporation). Twenty consenting stores were allocated to the 12-week intervention (7-point Healthy Stores 2020 strategy) or to usual retail practice. Four intervention stores with retail competition implemented a modified 6-point strategy. Weekly sales data were used to assess intervention impact on free sugars (g) to energy (MJ) (primary outcome) derived from all purchased food and beverages. Impact on gross profit and sales of targeted food and beverages was also assessed. Managers of intervention stores were interviewed to determine their views on customer response and impact on retail practice. Results: Free sugars were reduced by a relative 2.8% (95% CI -4.8, -0.7). There were significant reductions in free sugars from targeted beverages (-6.4%; -11.1, -1.5) and soft drinks (-12.5%; -18.1, -6.5). Gross profit was not impacted adversely. Managers mostly viewed the strategy favourably and of benefit to the community. Conclusions: The public health and business relevant gains demonstrated by this novel trial have resulted in ALPA converting their stores to the Healthy Stores 2020 strategy and integrating the strategy in to their nutrition policy. Retail competition impedes complete implementation of the 7-point strategy. Tackling this will require collective agreement by retailers to implement the full strategy and/or government policy power. Key messages: Restricting merchandising of unhealthy foods can achieve both public health relevant and business relevant gains. Working in partnership with retailers is critical to testing real-world interventions to impact population diet.